Multilingual communication in Speech Language Therapy - Sione Twilt; Karin Neijenhuis; Jan ten Thije; Rick de Graaff (Dutch Journal of Applied Linguistics, 2023)
Multilingualism can both enrich and complicate interactions in health care. Several studies (Ferguson, 2002; Jacobs, 2017) point out that language differences between care providers and patients can lead to less access to and lower quality of care. More specifically, challenges regarding communication, mutual understanding and shared decision making are often present (Cox & Maryns, 2021; Schouten et al., 2017) in health care situations.